2008 47th IEEE Conference on Decision and Control 2008
DOI: 10.1109/cdc.2008.4738973
|View full text |Cite
|
Sign up to set email alerts
|

Norm optimal Cross-Coupled Iterative Learning Control

Abstract: Abstract-In this paper, we focus on improving contour tracking in precision motion control (PMC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…In [9] it is concluded that the smallest error is achieved if W u = 0, however W u = 0 is used in order to handle model errors. Moreover, it is discussed that the convergence rate mostly depends on λ, where λ = 0 gives deadbeat control w.r.t the iterations and λ → ∞ makes the convergence rate arbitrarily slow.…”
Section: Stability Analysismentioning
confidence: 99%
“…In [9] it is concluded that the smallest error is achieved if W u = 0, however W u = 0 is used in order to handle model errors. Moreover, it is discussed that the convergence rate mostly depends on λ, where λ = 0 gives deadbeat control w.r.t the iterations and λ → ∞ makes the convergence rate arbitrarily slow.…”
Section: Stability Analysismentioning
confidence: 99%
“…Using analysis provided in [72,78] it can be shown that the S weighting matrix should be designed to ensure robust monotonic convergence in the presence of model uncertainty. Assuming a weighting matrix of the form S = sI, the weighting gain s provides constant weighting for uniform model uncertainty.…”
Section: Motivationmentioning
confidence: 99%
“…As is shown in [73], the influence of stochastic disturbances can be minimized by reducing the convergence speed. In [78] the dominating factor in convergence speed was shown to be the R weighting matrix. While a constant weighting gain r in R = rI provides consistent influence on the effect of stochastic disturbances, many applications include external disturbances and noise that change …”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations